Speaking Anxiety of English Department Students - Syarifuddyn, Tegar Aji (RETAIN, 2022)
The experts introduced the theory of anxiety which is considered to hinder students' ability to learn speaking English. On the other hand, speaking is an important aspect in mastering English. In this case, the study was conducted to measure the level of anxiety in students and the correlation between anxiety and perceived speaking ability. The research was conducted on second year English students at the State University of Surabaya. In this study, thirty students (7 boys & 23 girls) filled out the first questionnaire about class activities that focus on speaking. The Foreign Language Classroom Anxiety Scale (FLCAS) was used in this questionnaire. The average value is used to measure the anxiety’s level. The second questionnaire is intended for students to fill in their respective speaking skills according to how they feel. Pearson Correlation is used to determine the correlation between the two. The result show the students' level of anxiety is in a moderately relaxed position, but the relationship between anxiety and perceived speaking ability have a negative correlation. This is contrary to the results of previous studies which stated that speak in front of the others in the class activity is a main source of anxiety.